2017
DOI: 10.1016/j.fcr.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Water use and environmental parameters influence proso millet yield

Abstract: Proso millet (Panicum miliaceum L.) is a short-season, drought-tolerant C4 species capable of making use of limited available water supplies and is suitable for dryland crop rotations in the Central Great Plains. Previously published water use/yield production functions for proso millet have slopes lower than reported for other C4 species in this region. The objectives of this experiment were to determine the water-limited yield relationship for proso millet and to identify environmental factors that cause yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…Additionally, in the current study we found the climatic factors, excepted precipitation, seldom affect the spring wheat yield (the regression analysis results are not shown). It indicates that other climatic factors under extreme conditions occur seldom and they would not affect on crop production function for spring wheat in the study area, which contradicts the research of Nielsen & Vigil (2017b), in which water use-yield relation was affected greatly by a series of climatic factors, especially maximum temperature. Furthermore, in previous researchers, the non-linear relation between water use and crop yield is generally attributed to fluctuated soil evaporation which does not contribute to plant growth throughout the crop life cycle.…”
Section: Discussioncontrasting
confidence: 72%
“…Additionally, in the current study we found the climatic factors, excepted precipitation, seldom affect the spring wheat yield (the regression analysis results are not shown). It indicates that other climatic factors under extreme conditions occur seldom and they would not affect on crop production function for spring wheat in the study area, which contradicts the research of Nielsen & Vigil (2017b), in which water use-yield relation was affected greatly by a series of climatic factors, especially maximum temperature. Furthermore, in previous researchers, the non-linear relation between water use and crop yield is generally attributed to fluctuated soil evaporation which does not contribute to plant growth throughout the crop life cycle.…”
Section: Discussioncontrasting
confidence: 72%
“…Low water availability has a lesser effect on PM yield compared to other crops, and its yield increases with additional water at a rate of 132 kg/ha/cm. Yield response to water use of PM was 32.57 kg/ha/mm, which is higher than the other C4 crops, like corn 25.7 kg/ha/mm and grain sorghum 30.2 kg/ha/mm [11]. This indicated that PM has higher water-use efficiency than other C4 crops corn and sorghum.…”
Section: Droughtmentioning
confidence: 85%
“…It also allows PM to adapt and grow without using much subsoil water and mostly relies on early summer rains. Due to this, the soil moisture level at planting can be used to predict grain yield as it responds more considerably to soil water at the time of planting when compared to crops such as corn, sunflower and sorghum [10,11,29].…”
Section: Droughtmentioning
confidence: 99%
See 2 more Smart Citations